Quantification Prediction Soil Losses in Nakhon Ratchasima, Thailand - Kongkhiaw, Phatsakrit; Yossapol, Chatpet; Tantemsapya, Netnapid; Tran, Chau Ngoc; Tanang, Sirilak (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 3 (2021): July-September 2021, 2021)
Soil loss, accelerated by human activity, has become one of the world's most serious environmental problems because it poses significant threat to natural resources and the environment. This research focuses on soil loss in the future for sustainable land use planning for 9 watersheds over 20 years in Nakhon Ratchasima, Thailand. The integrated CA-Markov with GIS was applied to forecast 9 types of land use changes to analyze for soil conservation factors as of International Land Loss Equation (USLE). The land use change maps in 2019, 2023, 2027, 2031, and 2035 had been projected for land use predictions from 2011 and 2015 databases. The validation for the correctness of the production land use change map has 91.46% accuracy. The soil loss analysis of targeted study targets were divided into soil loss for the 9 watersheds and covers the overall provinces to determine the proportion of sediment generated in each watershed encountered the risk. The simulation results showed that the soil loss for the entire province may reach the highest soil loss at 329,271 T·km - 2 ·y - 1 with the mean at 2,929.06 T·km - 2 ·y - 1 . The amount of soil loss in 2035 will be 551.26 x 10 6 T·y - 1 . In terms of soil loss of all 9 water watersheds, LTK was found the highest soil loss with 238,606 T·km - 2 ·y - 1 . The average soil loss is estimated at 135.33 x 10 6 T·y - 1 , accounting for 25% of the total area. In comparison among the watershed areas, the amount of soil loss in LPP with highest soil loss rate per area at 51,100.51 ton per area per year. The future land use maps can be used to assess soil loss and can serve as an early warning system. The determination of policies to prevent future environmental problems is critical to controlling improper changes or adversely affecting the local environment.